2022
DOI: 10.31083/j.jomh1810195
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Prevalence of Metabolic Syndrome Based on Leg Strength, Cardiorespiratory Fitness, and Skeletal Muscle Mass in Elderly

Abstract: Background: Metabolic syndrome (MetS) is characterized by abdominal obesity, high blood glucose, and dyslipidemia. Low fitness, muscle mass, and strength increase the risk of MetS. The characteristics of these variables are highly interrelated. This cross-sectional study aimed to analyze the prevalence of MetS by combining leg strength (LSTR), cardiorespiratory fitness (CRF), and appendicular skeletal muscle mass (ASM) in elderly men and women. Methods: Participants included 1420 persons aged 65-79 years (men:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
2
0
0
Order By: Relevance
“…In a model of atherosclerotic occlusive disease (ASO), curcumol administration significantly improved arterial morphology, reduced stenosis, and suppressed autophagy in femoral arteries. Histological analyses demonstrated that curcumol‐treated arterial tissue exhibited a more organized endothelium, well‐arranged endothelial cells, and minimal membrane thickening, compared with the ASO model 21 . These outcomes further confirmed our in vitro studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In a model of atherosclerotic occlusive disease (ASO), curcumol administration significantly improved arterial morphology, reduced stenosis, and suppressed autophagy in femoral arteries. Histological analyses demonstrated that curcumol‐treated arterial tissue exhibited a more organized endothelium, well‐arranged endothelial cells, and minimal membrane thickening, compared with the ASO model 21 . These outcomes further confirmed our in vitro studies.…”
Section: Discussionsupporting
confidence: 84%
“…Histological analyses demonstrated that curcumol-treated arterial tissue exhibited a more organized endothelium, well-arranged endothelial cells, and minimal membrane thickening, compared with the ASO model. 21 These outcomes further confirmed our in vitro studies. Prior study has indicated that the small molecule receptor tyrosine kinase inhibitor sunitinib restricts neointimal hyperplasia in balloon-injured rat carotid arteries.…”
Section: Discussionsupporting
confidence: 80%